Yoke-shaped MgO-barrier magnetic tunnel junction sensors - COEY, JOHN (My University, 2012)
Yoke-shaped sensors based on MgO-barrier magnetic tunnel junctions have been designed, fabricated, and studied; they show a good linear tunneling magnetoresistance (TMR) response. A nearly-perpendicular configuration of two ferromagnetic electrodes was set by two-step annealing together with shape anisotropy. The low-frequency noise characterization shows these yoke-shaped TMR sensors have relatively low magnetic 1/f noise. The field sensitivity is up to 27%/mT, while the field detectivity reaches 4.6 nT/Hz‾‾‾√ at 10 Hz and 460 pT/Hz‾‾‾√ at 1 kHz. These TMR sensors may be useful for applications such as biomagnetic detection.
PUBLISHED
Keywords: Magnetic tunnel junctions